Incomplete Gamma distribution of rainfall for sustainable crop production strategies at Palampur, Himachal Pradesh (MAUSAM, 2009)
The knowledge of rainfall pattern (amount and probability) helps in planning of crops to be grown in a region. Therefore weekly, monthly, seasonal and annual rainfall data for 33 years (1974-2006) for the station Palampur have been collected and its analysis has been attempted.  The annual and monthly rainfall data were analyzed for finding out drought normality and abnormality. The analysis indicated that the rainfall is mainly confined in annual rainfall       2343 mm with 25.7 per cent variability. The standard deviation of annual rainfall is 62.8 mm. Each standard week from 26th to 35th receive a rainfall of more than 100 mm, indicating the crop period. Seed sowing in paddy nursery in the Palampur region generally takes places immediately after initiation of monsoon during 23rd - 25th standard meteorological weeks and transplanting is carried out around 27th or 28th standard meteorological week. The tillering, 50 percent flowering and dough stage are observed during 32-33rd, 37-38th and 40-41st  standard meteorological weeks respectively.